The Influence of the Role of Parents and Peers on the Self-Concept of High Grade Students at SD N Klumprit 1 - Sulistiyo, Gangsar Imam; Muhroji, Muhroji (Al Hikmah: Journal of Education, 2022)
The purpose of this study was to determine: to analyze the influence between the role of parents on the self-concept of high grade students at SD N Klumprit 1, to analiyze the influence between peers on the self-concept of high-class students at SD N Klumprit 1, to analyze the influence between the role of parents and peers on the self-concept of high-class students at SD N Klumprit 1. The method used in this study is quantitative with measuring instruments in the form of self-concept scale, parental social support scale, and peer interaction scale. The results showed that the analysis of the parental role variable with the self-concept variable seen from the correlation value (r) = 0.696, it can be said that there is a positive influence between the role of parents on self-concept, analysis of peer variables with self-concept variables seen from the correlation value (r) = 0.725, it can be said that there is a positive influence between peers on self-concept. The F statistical value of the influence of the role of parents and peers on students' self-concept is greater than F table (3.15) which is 56.957, it can be said that there is a significant influence of the role of parents and peers on the self-concept of class students height SD N Klumprit 1.